Eksplorasi Perumpamaan Dirham yang Hilang: Refleksi berdasarkan Lensa Pendidikan Agama Kristen - Sarmauli, Sarmauli; Lana, Isa Andreyanku (Sekolah Tinggi Teologi Parakletos Tomohon, 2024)
Abstract: This research is motivated by the author's curiosity to explore the contemporary meaning of the content of the parable of the prodigal son in Luke 15:8-10, which has become a topic of discussion in Christianity. This parable illustrates God's love for a lost soul and conveys moral and spiritual messages that are relevant in the context of modern Christian life. The purpose of this research is to explore the meaning of the parable of the lost dirham in the Gospel of Luke in the controversy or phenomenon of contemporary Christianity. The research method in this paper uses a qualitative approach through literature review to explore the moral and spiritual messages contained in this parable and its relevance in contemporary Christian religious education. The findings confirm that the parable emphasizes the infinite love of the Creator for each individual who feels